The legal foundations of nature as a subject of rights and its constitutional interpretation in the Ecuadorian context - Moreira Moreira, Erika María (Frónesis, 2022)
Nature has been considered an anthropocentric theory over time, and the evolution of law, conditioning itself on philosophical positions, constitutional principles and doctrinal foundations, by virtue of the promulgation of the Constitution of the Republic of Ecuador, recognition granted by the Constituent power through the National Assembly of the aforementioned country in Montecristi, Manabí province, became as of 2008 a democratic, multicultural, secular regulation, containing in itself, normative precepts that protect it as a holder of rights. In this study, affirmative public policies will be proposed to the scientific community to solve situations aimed at the violation of environmental rights that are caused by humans. From the exhaustive search of diverse original bibliographic sources, the main reasons will be identified, for which, nature has not been alluded from its beginnings as a subject of rights, the legal relationship between its native components and the actions of the human being. Concluding that, the expected results will distinguish nature as a fundamental part of a process, but, it does not act as a defendant, but, as plaintiff, represented by any citizen who demands respect for the legal system, and that or there is violation to their fundamental rights or their intrinsic value.